Financial market rates and flows - James C. Van Horne (Prentice Hall International, Inc., 2001)
This book explores the behavior of interest rates as they relate to changing market conditions, and examines how risk can be managed. It successfully bridges the gap between interest-rate theory and its application to fixed-income security portfolio management. Coverage includes the function of financial markets, the flow-of-funds system, foundations for interest rates, inflation and returns, derivative securities, the influence of taxes, and the social l allocation of capital. For those in the financial community, in business, and in government, who are concerned with investing in or issuing fixed-income securities.
Donated by: Anvar Hodjaev